Beberapa faktor yang berhubungan dengan kejadian hepatitis B dan C pada pendonor darah - Theodola Baning Rahayujati, Siti Nurdjanah, Nawi Ng (Berita Kedokteran Masyarakat (BKM), 2006)
Background: Hepatitis B virus (HBV) and Hepatitis C virus (HCV) infection transmitted through blood product remains the major infectious problems in developing countries. There was an increase of HBsAg and anti-HCV prevalence among blood donors in Yogyakarta in the last five years. Objective: of this study was to identify factors associated with HBV and HCV infections in this group. Methods: This cross sectional study was conducted among blood donors in five units of blood transfusion unit in the Yogyakarta Municipality Red Cross. The status of HBV infection was ascertained with the presence of HbsAg using EIA or immunochromatography, and HCV infection was determined by the presence of anti HCV using Enzyme lmmuno Assay (EIA) or rapid test, Histories of blood transfusion, use of injection needles, tattooing, body piercing, acupuncture, dental treatment. family history of hepatitis, sexual activities, and use of shared tooth brushes and razor blades were collected using questionnaire. Result: Out of 805 subjects screened 2.2% and 0.6% were HBV positive and HCV positive, respectively. Only sexual activity with partners other than spouse was significant predictor of infections in the multivariate analysis (ORwyr-5,86, 95%CI 2,10-16,34 and ORHevr. 14.62; 95% CI 2,29-93,45). Conclusion: The high prevalence of HBV and HCV infections among blood donors found in this study should alert public health practitioner. Providing health education on reproductive health and risk of sexual transmission of HBV and HCV should therefore be among the major focuses of health authority. Keywords: Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), Blood Donors, HBsAg, anti-HCV